Modernizing the Indian sewerage system – proposal for vocational training and licensing of sanitation professionals: A step toward dignity, safety, and recognition - Raman Kumar (Journal of Family Medicine and Primary Care)
Sanitation workers play a crucial role in the functioning of India’s urban and rural public health systems. They are responsible for waste collection, sewer maintenance, drain cleaning, public toilet sanitation, and other essential hygienic services. According to the National Commission for Safai Karmacharis (NCSK), 113 persons have lost their lives during the past 2 years, 2023 and 2024, due to hazardous cleaning of sewer and septic tanks. These deaths are often caused by suffocation, inhalation of toxic gases like methane and hydrogen sulfide, and falls into open trenches, with negligible safety measures in place. While India has enacted laws such as the Prohibition of Employment as Manual Scavengers and their Rehabilitation Act, 2013, gaps remain in enforcement and occupational safety. The absence of a formal recognition and certification system has perpetuated informality in this workforce. This proposal aims to introduce a structured Sanitation Worker Licence nationwide as a step toward ensuring dignity, safety, and professional recognition for sanitation workers. Modernizing sewer systems is crucial for addressing sanitation challenges, improving public health, and promoting sustainable urban development. India’s reforms must pivot from reactionary measures to proactive, technological solutions that elevate safety standards and operational efficiency.